Application of digital technology in the early diagnosis and treatment of knee osteoarthritis - WU Yi; SHEN Siyuan; LIANG Feng; XIAO Shouyun; TIAN Jiwei; DING Huimin (Zhongguo linchuang yanjiu)
Knee osteoarthritis (KOA) is one of the common diseases among middle-aged and elderly people, mainly characterized by knee swelling, pain, and functional impairment. The process of KOA is progressive and irreversible. Timely identification and effective intervention in early KOA are crucial for improving patients' quality of life and slowing down the disease progression. With the rapid development of digital technology, its application in the medical field has become increasingly widespread, especially in the diagnosis and treatment of early KOA. In recent years, digital tools have been continuously innovated, including mobile health applications, remote monitoring technologies, and artificial intelligence assisted diagnostics. These technologies not only improve the efficiency of early identification in KOA, but also provide real-time monitoring and personalized interventions for patients. However, the application of digital technology faces multiple challenges such as data privacy, technology integration, and clinical applicability. This article reviews the current research progress of digital technology in the diagnosis and treatment of early KOA, aiming to provide new perspectives for clinical practice, highlight the direction and challenges for future research.